Adipokines: Endocrine relationship between obesity and type II diabetes - Silva Jr, Autran José (2017)
Study Model: literature review. Introduction: Adipose tissue produces many peptides and non-peptides called adipokines that act on metabolic control and activity. Aim: The study aims an explanatory model that links obesity with type 2 diabetes from these adipokines. Methodology: The literature review consisted of consultation in databases: Scientific Electronic Library Online (Scielo) Highwire, PubMed in January 2000 period to date. Two analyzes were performed, the first used the descriptors obesity and adipokines and type 2 diabetes and adipokines, for a total of 6 combinations. The need for a second analysis was because the first were observed an excessively large number, and so needed a new refinement. The descriptors and their combinations in Portuguese, English and Spanish literature used for selection in the second analysis in the electronic media were: obesity and type 2 diabetes and tumor necrosis factor; obesity and type 2 diabetes and interleukin 6; obesity and type 2 diabetes and resistin; obesity and type 2 diabetes and adiponectin. Results: We selected 40 articles, which were related to obesity, diabetes and adipokines. Conclusion: The proposed model appears to be consistent, because numerous studies individually relate the effects of adipokines. Knowing these effects, releasing and inhibiting factors and the proposed model, it is essential for a good understanding of the association between the two conditions studied and thus propose new methods of control.